Reserved and Irreverent. Some Considerations on Erving Goffman’s Ethnographic Writing Style - Toscano, Giuseppe (Italian Sociological Review, 2019)
Discretion and irreverence are two generally recurrent features when one refers to Erving Goffman. Even if their juxtaposition seems unlikely, both characteristics are strictly connected: they reveal the distinguishing trait of Goffman’s sociological gaze. The aim of this paper is to consider discretion and irreverence not only as hallmarks of the public presentation of Goffman’s self, but as methodological choices in developing his unique ethnographic writing style. Comparing Goffman’s way of writing to classical ethnographic writings, one will realize that they are very different: Goffman’s ethnographies are definitely more discreet, but his discretion actually underlies an irreverent, critical and desecrating eye. Staying in the shadows and ‘watching how people snore’, Goffman leads an attack both on the taken for granted assumptions of traditional ethnography, and on hierarchies and legitimate boundaries between social worlds. He violates the boundaries between highbrow culture and lowbrow culture, between sociology and literature; but what is most disquieting, is his violation of the borderline that divides reality from fiction.